Jump-Starting Self-Employment ? : Evidence Among Welfare Participants In Argentina - Galasso, Emanuela (The World Bank, 2007)
One important concern of governments in developing countries is how to phase out large safety net programs. The authors evaluate the short-run effects of one possible exit strategy-programs that promote self-employment-in Argentina. They provide evidence that a small fraction of beneficiaries were attracted by this program. Overall, potential participants to self-employment are more likely to be female household heads and more educated beneficiaries relative to the average Jefes beneficiaries. Using nonexperimental methods, the authors show that participation in the program does affect the labor supply of participants, by reducing the probability of having an outside job, especially for males, and increasing the total number of hours worked. But the intervention fails to produce on average income gains to participating individuals and households in the short run. The fact that a small subset of former welfare beneficiaries are attracted to the program, coupled with the fact that only a subset of participants (younger and more educated beneficiaries, and with previous self-employment experience) benefited from participation has important implications for this intervention to represent a viable exit strategy from welfare